1998
DOI: 10.1180/claymin.1998.033.4.04
|View full text |Cite
|
Sign up to set email alerts
|

Source of Palygorskite in Gypsiferous Aridisols and Associated Sediments from Central Iran

Abstract: Arid soils in central Iran that evolved from the weathering of post-Tethyan sediments contain palygorskite. Clay fractions of gypsiferous soils and their associated sediments from different landforms from central Iran were investigated. Palygorskite was the dominant silicate clay mineral in clay fractions of the soils, and of Oligo-Miocene limestone, a less common parent rock. The Jurassic shale and Cretaceous limestone contain illite and chlorite with a trace amount of palygorskite. Association of large amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 37 publications
9
53
0
Order By: Relevance
“…The association of smectite and palygorskite in the Oligo-Miocene limestone and marl is consistent with the results of others (Gindy et al, 1985;Shadfan et al, 1985a,b,c;Shadfan and Mashhady, 1985;Ingles and Anadon, 1991;Pletsch et al, 1996;Khormali and Abtahi, 2003). Khademi and Mermut (1998) found palygorskite and sepiolite and appreciable amounts of mica and smectite in the clay fraction of the Oligo-Miocene limestone of central Iran. All formations contained small quantities of interstratified minerals, but only the youngest contained measurable amounts of quartz.…”
Section: Mineralogy Of the Sedimentary Rockssupporting
confidence: 90%
See 2 more Smart Citations
“…The association of smectite and palygorskite in the Oligo-Miocene limestone and marl is consistent with the results of others (Gindy et al, 1985;Shadfan et al, 1985a,b,c;Shadfan and Mashhady, 1985;Ingles and Anadon, 1991;Pletsch et al, 1996;Khormali and Abtahi, 2003). Khademi and Mermut (1998) found palygorskite and sepiolite and appreciable amounts of mica and smectite in the clay fraction of the Oligo-Miocene limestone of central Iran. All formations contained small quantities of interstratified minerals, but only the youngest contained measurable amounts of quartz.…”
Section: Mineralogy Of the Sedimentary Rockssupporting
confidence: 90%
“…Khademi and Mermut (1998) discussed three ideal conditions for palygorskite formation in soils and sediments of central Iran: (1) Increase in Mg/Ca ratio due to gypsum crystallization in the shallow water bodies; (2) Increasing environmental pH due to warm climate; and (3) Increasing soluble Si due to enriched hydrothermal solutions. Eswaran and Barzanji (1974) showed that neoformed palygorskite fibers coat gypsum and hornblende crystals.…”
Section: General Clay Mineralogy Of Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many soils from semiarid regions of the world, palygorskite has been reported with increasing frequency. In these environments, two main mechanisms have been proposed to explain the presence of palygorskite: (1) a detrital origin [48,49], i.e., the occurrence of palygorskite is attributed to palygorskite-bearing rocks, sediments, or soils, allochthonous or inheritance, and (2) an in situ pedogenic origin [24,50,51]. Allochthonous or inherited palygorskite provides insight into the evolution of the paleoclimate of the source area, whereas in situ authigenic palygorskite documents information on the paleoclimate of the depositional region.…”
Section: Palygorskite Genesismentioning
confidence: 99%
“…1993;Molinaroli and Irba 1995;Singer et aI. 1995;Verreechia and Le Coustumer 1996;Khademi and Mermut 1998). In general, the two clay minerals occur in the lower parts of caliche profiles, having been dissolved nearer to the surface, and they are precipitated during the dry season but dissolve during the humid part of the year (van den Heuvel 1966;Newman 1987;Gauthier-Lafaye et aI.…”
Section: Sepiolite and Palygorskitementioning
confidence: 99%